Nitrogen, Phosphorus and Potassium Deficiencies Impact the Transition from Juvenility to Maturity in Theobroma cacao L - Maya Weinstein; Shahar Baram; Uri Yermiyahu; Ludmila Tsehansky; Assaf Elmakias; Ellen R. Graber (International Journal of Fruit Science)
The juvenile to mature transition is a pivotal stage in the life cycle of Theobroma cacao L. A controlled greenhouse experiment was conducted to study the effects of nitrogen (N), phosphorus (P) and potassium (K) on this transition, denoted by formation of the jorquette, in young cacao shoots. Five N levels, two P levels and two K levels were evaluated. Stem growth, drainage volume, and irrigation and drainage water chemistry were determined periodically. The apical meristem was examined routinely for initiation of the jorquette. The treatments did not affect growth, but the difference in time to jorquette between the lowest and highest N treatments was 6 months, an increase in time of 87%. Low P treatment also delayed the transition (338 versus 227 days, a 49% increase in time). At the lowest N dose, 40% of the trees did not mature by the experiment end (468 days). Significant delays in maturation due to insufficient nutrients can have negative ramifications for cacao yield, and particularly when is followed by delays in flowering onset caused by nutrient deficiencies. Optimizing nutrient availability at different cacao growth stages could improve yield, guide planting and fertilization, improve plot management and facilitate fruit harvest.